2011
DOI: 10.3389/fpsyg.2011.00148
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Cognitive Dysfunction in Schizophrenia – is there a Link?

Abstract: Cognitive dysfunction is a well recognized symptom of schizophrenia, as well as patients having poor insight into their illness. The subjective scale to investigate cognition in schizophrenia (SSTICS) is one of several scales that have been developed to study subjective cognitive dysfunction and has been compared to patients’ objective cognitive level. A literature search was performed using PubMed, psychINFO, Web of Science, and cross-referencing to find 26 articles which used 14 different subjective cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 82 publications
3
25
1
1
Order By: Relevance
“…Supporting our first hypothesis, objective and subjective cognitive functions were found not correlated with each other. This is in keeping with previous studies that also did not find significant associations (Chang et al, ; Homayoun et al, ). Note that this pattern of results was as well replicated in people across various conditions other than psychosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Supporting our first hypothesis, objective and subjective cognitive functions were found not correlated with each other. This is in keeping with previous studies that also did not find significant associations (Chang et al, ; Homayoun et al, ). Note that this pattern of results was as well replicated in people across various conditions other than psychosis.…”
Section: Discussionsupporting
confidence: 93%
“…Some people with schizophrenia who complain about their cognitive functioning did not actually show cognitive deficits on objective cognitive measures (Holthausen et al, ). Homayoun, Nadeau‐Marcotte, Luck, and Stip () reviewed 26 studies and only half showed an association between OCI and SCI. Other individual studies also reported a relatively weak to null association in schizophrenia (Chan et al, ; Prouteau et al, ; Stip, Caron, Renaud, Pampoulova, & Lecomte, ).…”
Section: Introductionmentioning
confidence: 99%
“…Les résultats de la présente méta-analyse ne corroborent pas cette hypothèse, et suggèrent plutôt que le manque de conscience des déficits neurocognitifs et le manque d'autocritique par rapport à la « maladie » sont des phéno-mènes largement indépendants. En 2006, Stip a formé le terme de « schizo-anosognosie » afin de départager le manque d'autocritique par rapport aux déficits cognitifs du manque d'autocritique tel qu'on le conçoit traditionnellement, soit le manque d'autocritique par rapport à la « maladie » (Homayoun et al, 2011). Les résultats de la présente méta-analyse confortent la pertinence du concept de schizo-anosognosie, de même que les efforts investis dans la littérature métacogni-tive afin d'identifier les différentes formes de manque d'autocritique dans la schizophrénie (Gilleen et al, 2011).…”
Section: Discussionunclassified
“…Schizophrenia is a psychiatric disorder characterized by positive and negative psychopathological symptoms and cognitive deficits . Many instruments have been developed for the assessment of cognitive functions in patients with schizophrenia . Among them, the Brief Assessment of Cognition in Schizophrenia (BACS) is a concise tool designed to evaluate cognitive functions that are characteristically impaired in patients with schizophrenia …”
Section: Summary Of Whole‐brain Correlation Analyses Using Comprehensmentioning
confidence: 99%